Effects of isocaloric carbohydrate-protein versus protein recovery drink on muscle function following resistance exercise - Tan, Ci Hui (2015)
Intense resistance exercise (RE) can reduce muscle glycogen content and cause muscle damage, affecting muscle functional performance. Post-exercise ingestion of protein (PRO) and/or carbohydrate (CHO) may enhance muscle recovery, but its effects on subsequent performance are debatable. This study aimed to compare the effects of a carbohydrate-protein (CHO-PRO) and isocaloric PRO drink on the recovery of muscular strength, power and endurance in young women, following an acute RE bout. It was hypothesised that both CHO-PRO and PRO would induce greater recovery of muscle function (MF) compared to control (CON), but there would be no difference in recovery when comparing between CHO-PRO and PRO. Seven untrained women (Mean ± SD: Age = 21.9 ± 0.4 years, BMI = 20.8 ± 1.7 kg/m2) randomly ingested a PRO, CHO-PRO or CON drink immediately after completing 4 sets of 10 repetitions of deadlift, leg press, leg curl and leg extension at their 10-repetition maximum. Extensor peak torque, work per repetition, average power and total work were measured immediately and 3-hour post-RE using an isokinetic dynamometer. Data were analysed using one-way repeated-measures ANOVA, with an alpha of 0.05. When compared with baseline, net decrements in MF post-RE were generally not significant (0.060 ≤ p ≤ 0.781). No significant differences (0.067 ≤ p ≤ 0.969) were found in the recovery of functional performance across conditions. The results indicated that PRO and CHO-PRO did not result in greater post-exercise recovery of muscular strength, power and endurance in untrained women, compared to CON.